Exploring Equity and Inclusion in Canadian and Quebecois Contexts - Zaky, Radamis; Somda, Aris (Université d'Ottawa | University of Ottawa, 2024)
This open-source resource is mainly designed for communication students who are studying organizational communication and primarily focused on the Canadian context. It fills an important need as most of the available textbooks are mainly American-focused textbooks and as a result, do not properly represent the complexities of the Canadian context. This resource is divided into four chapters. The first one provides different definitions and explanations for equity, diversity, inclusion, and decolonization (EDID). The second chapter focuses on the existing legal frameworks that are meant to legally organize EDID in both Canada and Québec. The third chapter focuses on the importance of the culture of EDID as legal frameworks alone will not achieve effective EDID. Chapter 3 also provides readers with some practical recommendations for best practices that organizations can use to achieve EDID for hiring practices. The last chapter focuses on the ramifications on mental health when EDID is not achieved.
Keywords: diversity; inclusion; decolonization; equity; communication; Open educational resource (OER)